PENGEMBANGAN BAHAN AJAR TEKNOLOGI INFORMASI DAN KOMPUTER BERBASIS PROJECT BASED LEARNING BAGI MAHASISWA - Anna Mariyani; Tio Ikhtiar Tiantoko; Muhammad Aunur Rofiq (JURNAL SINEKTIK, 2021)
This research aims to develop a textbook on Informatics and Computer Technology with a selfregulated learningapproach. The study used the  RnD method through a 4D model. The defining stage(define)byestablishing the characteristics of the teaching book to be developed through initial study. The design stage,choosing the format and design of the teaching book to produce thefirstcorrection (draft).   The development stage (develop) to produce the second correction(draft), the third correction, and the final product of the teaching book. Based on the results of field tests on students who are taking Computer Technology and Information courses obtained the final product from the teaching book. One of the features and devices of the teaching book developed is the project task feature. Based on validation of teaching books and supporting devices produce criteria are very feasible and ready to be used and guide students' learning through the features in the teaching book. The development of this teaching book is expected to help in developing not only in Informatics and Computer Technology materials but also in other materials that use computers.